(untitled) (Historia, 2021)
Savings and survival in a modern African economy: informal savings organisations and poor people in South Africa It is not normally assumed that informal savings organisations function in developed economies, since they are perceived to be relatively exclusive to developing economies. This study disputes some perceptions in the current international literature on such organisations when compared to the modern South African experience. Informal savings organisations are also not exclusive to poor people, although the majority of participants have low or irregular incomes. This v.study reflects on the current literature in the light of research undertaken in the Gauteng province. It indicates a higher savings propensity than is currently acknowledged and calls for further research to facilitate economic empowerment